Revisiting the Causal Nexus between Defense Expenditure and Economic Growth: Time Series Analysis for Saudi Arabia - Ping, Guo; M, Alotaish Mohammed Saud (Asian Journal of Economic Modelling, 2016)
This time series study analyzed the effect of defense expenditure on GDP, oil GDP and non-oil GDP of Saudi Arabia. The defense expenditure is introduced as explanatory variable in production function for said purpose. This study used time series data from 1969 to 2013 and unit root test determined that variables of the study share same integration order. Long run relationship was established among variables through cointegration test. Dynamic ordinary least squares results showed that defense expenditure positively affect GDP and non-oil GDP in the long run while its impact on oil GDP is insignificantly positive. The causality analysis confirmed that defense expenditure has direct and indirect effect on GDP in Saudi Arabia as defense expenditure causes GDP, oil GDP, non-oil GDP, investment, and labor force in the long run. This study concluded that defense expenditure is as one of the factor of the economic growth in Saudi Arabia.